Social Networking Postings: Views from School Principals - Griffin, Marlynn M.; Lake, Robert L. (Education Policy Analysis Archives, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Numerous recent media accounts indicate that teachers are being fired, put on probation, or otherwise censured because of information found on their social networking sites (SNS). While the literature in business, psychology, and pharmacy shows initial investigations of the impact of SNS information on hiring decisions, this area has not been investigated in the field of education. Data from pre-service teachers’ SNS were compiled into a 51-item questionnaire and K-12 school principals rated each statement on its likelihood to influence a hiring decision if it were found on the SNS of a teacher applying for a position at his or her school. The statements included on the questionnaire included sexual talk, swearing, violent language, references to drugs and/or alcohol use, and language that could be considered pejorative to individuals with disabilities, persons of color and/or homosexual individuals. The findings of this preliminary study indicate that of the 51 statements, 28 had average ratings in the moderate-to-significant impact on hiring decision range and 22 had average ratings in the minor-to-moderate impact on hiring decision range. Only one item of the 51 fell in the no impact-to-minor impact on hiring decision range. Findings are discussed in relation to professional dispositions, categories of information that may influence hiring decisions, and internet use policies. Implications based on the data from this study include the need to develop state and university policies for SNS use. Finally, the results of this study indicate that further research into hiring administrators’ use of data from SNS in hiring decisions is warranted.